Desentralisasi Fiskal dan Pertumbuhan Ekonomi di Indonesia - Kusuma, Hendra (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88)DO - 10.24843/JEKT.2016.v09.i01.p01)
The fiscal decentralization in Indonesia has been applied since 2000, the consequences of this policy are given the financial to local governments. However, there are several issues which are whether the delegation of authority given by the central government to the local governments that can contribute to economic growth in the region in the implementation of authority. The role of central government in helping economic growth in the region is reflected in the various kinds of funds transfer that is given, such as DAU, DAK and DBH. By using data of provinces in Java and Sulawesi between 2010 and 2013 and seeing the size of the decentralization of the proxy used is the capability area of the transfer in the creation of economic growth (AI I ) and the measure capability of local revenue in contributing to economic growth (AI II ), so that it will give more objective overview to economic growth in the region during fiscal decentralization. The result of estimation by using random effect indicate that the ratio of capital expenditures to total expenditures of local governments, indicator of fiscal decentralization represented the capability of funds transfer to the establishment of regional income and the contribution of local revenues to total revenues, concluding that fiscal decentralization in Indonesia have an impact on economic growth, especially the contribution of spending conducted by local governments.
Keywords: fiscal decentralization, funds transfer, economic growth, data panel